Hollow CoSe2 nanocages derived from metal–organic frameworks as efficient non-precious metal co-catalysts for photocatalytic hydrogen production. Issue 17 (8th August 2019) - Kim, Eun Hwa; Reddy, D. Amaranatha; Lee, Hwan; Jeong, Seonghyun; Kumar, D. Praveen; Song, Jae Kyu; Lim, Manho; Kim, Tae Kyu
Abstract : Hollow structured CoSe2 nanocages are developed as efficient co-catalysts for photocatalytic hydrogen productions. Abstract : Photocatalytic water splitting by semiconductor nanostructures is a challenging chemical process for harnessing abundant solar energy and obtaining clean H2 fuel. To this end, photocatalysts that comprise efficient light-harvesting semiconductor nanostructures and noble metal-free robust co-catalysts have attracted considerable attention. In this study, we designed a noble metal-free nanohybrid consisting of CdS nanorods (NRs) as photoabsorbers and CoSe2 nanocages as co-catalysts. Benefiting from suitable band edge potentials, abundant catalytically active sites, large surface area, and efficient photoexcited charge carrier transfer, the fabricated nanohybrid exhibited a remarkable photocatalytic H2 evolution performance (82.5 mmol h −1 g −1 ), which is approximately 37.5 times higher than that of bare CdS NRs. Moreover, the observed H2 evolution rate was even higher than those of even noble metal Pt-anchored CdS NR composites. Furthermore, the fabricated nanohybrid exhibited prominent recycling stability (50 h) under solar light irradiation. The key role of the co-catalyst, the effects of the catalyst dosage and scavenger concentration, and the origin of the photocatalytic H2 production were comprehensively investigated. We believe that this design is the prospective path toward the development of three-dimensional hollow-type noble metal-free nanostructures for enhancing H2 production.